A Novel Mutation of the α2-Globin Gene Causing α+-Thalassemia: Hb Nanning (HBA2: c.369_370delinsGA). (2nd January 2017) - Chen, Biyan; Lin, Li; Yi, Shang; Chen, Qiuli; Wei, Hongwei; Li, Guojian; Zheng, Chenguang; He, Sheng; Qiu, XiaoXia
Abstract: We report a novel mutation on the α2-globin gene, Hb Nanning ( HBA2 :c.369_370delinsGA) detected in a Chinese family. This mutation gives rise to a previously undescribed hemoglobin (Hb) variant that was undetectable by various separation techniques. Both carriers of the mutation have mean corpuscular volume (MCV) and mean corpuscular Hb (MCH) values that are below normal, as would be predicted for an α + -thalassemia (α + -thal) patient.